Optimized potassium application rate increases foxtail millet grain yield by improving photosynthetic carbohydrate metabolism - Li, Yanfen; Yin, Meiqiang; Li, Lulu; Zheng, Jungang; Yuan, Xiangyang; Wen, Yinyuan (Frontiers in Plant Science, 2022)
Photosynthetic carbohydrate metabolism is an important biochemical process related to crop production and quality traits. Potassium (K) critically contributes to the process of photosynthetic carbon assimilation and carbohydrate metabolism. We explored the effects of potassium fertilization on physiological mechanisms including carbohydrate metabolism in foxtail millet and its yield. Field experiments were performed using two foxtail millet (Setaria italica L.) cultivars: 1) Jingu 21 (low-K sensitive); and 2) Zhangza 10 (low-K tolerant). Effect of five different potassium fertilizer (K2O) rates (0, 60, 120, 180, and 240 kg·hm−2) were tested in two consecutive years, 2020 and 2021. We found that potassium application significantly increases the K content, shoot dry matter accumulation and yield. Jingu 21 and Zhangza 10 had maximum yields at 180 kg·hm−2 K application, which were 29.91% and 31.51% larger than without K application, respectively. Excessive K application (K240) did not further improve their yields. The suitable K fertilizer application of Jingu 21 and Zhangza 10 are 195.25–204.27 and 173.95–175.87 kg·K2O·hm−2, respectively. The net photosynthetic rate (Pn), ribulose-1,5-bisphosphate carboxylase-oxygenase (Rubisco), phosphoenolpyruvate carboxylase (PEPC), and fructose-1,6-bisphosphatase (FBPase) were positively correlated with the potassium content. Potassium application improved the availability of carbon sources for carbohydrate synthesis. Compared with the K0 treatment, variations in the activities of sucrose phosphate synthase (SPS) and sucrose synthase (SuSy) in potassium-treated Jingu 21 (K60, K120, K180, and K240) were 17.94–89.93% and 22.48–182.10%, respectively, which were greater than those of Zhangza 10 (11.34–71.12% and 16.18–109.13%, respectively) and indicate that Jingu 21 is more sensitive to potassium application. The sucrose contents in the Jingu 21 and Zhangza 10 grains were 0.97–1.15% and 1.04–1.23%, respectively. The starch contents were 28.99–37.75% and 24.81–34.62%, respectively. The sucrose : ratio of Jingu 21 was smaller than that of Zhangza 10, indicating that Jingu 21 utilized nutrients better than Zhangza 10. Stepwise regression and path analysis showed that leaf and grain SuSy activity, by coordinating the source-sink relationship, have the greatest direct effect on Jingu 21 yield, whereas leaf SuSy activity, by promoting the generation of photosynthates at the source end, plays a leading role in Zhangza 10 yield increase.